HIV/AIDS burden, attributable risk factors, and projections among reproductive-age adults in China, 1990–2035: A GBD 2023 analysis - Huibo Yan (PLoS ONE, 2026)
Background HIV/AIDS remains a leading infectious disease burden globally. While highly active antiretroviral therapy has transformed HIV into a manageable chronic condition, contemporary trends and attributable risk factors among reproductive-age adults in China—a critical demographic for epidemic control—remain poorly characterized. This study provides an updated comprehensive assessment of HIV/AIDS burden in this population using Global Burden of Disease Study 2023 data, which incorporates methodological refinements and post-pandemic data not available in earlier versions. Methods We extracted age-standardised incidence, prevalence, mortality and disability-adjusted life-years (DALYs) for Chinese adults aged 15–49 years from GBD 2023. Joinpoint regression estimated annual percent change and identified significant trend inflection points. Population attributable fractions were analysed for unsafe sex, drug use, and intimate-partner violence. ARIMA models forecasted burden trends to 2035 with 95% uncertainty intervals. Results Between 1990 and 2023, age-standardised rates increased substantially: incidence +301% (from 0.82 to 3.29 per 100,000), prevalence +774% (4.84 to 42.29), mortality +1,623% (0.13 to 2.24), and DALYs + 1,439% (7.96 to 122.48). Males showed consistently steeper increases than females across all metrics (all p < 0.05). Unsafe sex accounted for 70% of HIV/AIDS mortality in 2023. ARIMA projections indicate that while male incidence will plateau at ~5.0 per 100,000 by 2035, female metrics will continue rising (incidence +21%, prevalence +30%), widening the sex disparity. Conclusion China’s HIV epidemic has transitioned to a chronic disease burden. Notably, this burden shows pronounced sex differences. Mortality is rising among people living with HIV, particularly among women. These trends highlight urgent needs for gender-differentiated prevention strategies. Our findings provide measurable targets for China’s National HIV/AIDS Action Plan (2024–2030) and SDG 3.3 monitoring. They further demonstrate how standardized burden estimation supports precision public health.